Outer Surface Elongation of Flexspline and Its Influence on Harmonic Drive Meshing - Liu Mengfei; Du Qungui (Jixie chuandong)
The accurate calculation of the backlash of harmonic reducers is crucial for the study of transmission performance, load capacity calculation, and tooth profile design of harmonic reducers. The current research is based on the neutral line no-elongation theory, calculating the assembly of flexible gear tooth profile. Considering the fact that gear teeth grow in the flexspline outer surface, assembly will make flexspline outer surface deform, leading to deviation of gear teeth. In this study, the method for solving the no-load clearance is proposed based on the flexspline outer surface deformation. The results show that the new method for calculating the flexspline assembly may present tooth profile interference, which should be considered in tooth profile design or harmonic reducer design. The finite element method is used to verify the analytical solution, and the two results are basically consistent.